Development and Optimization of Solid Lipid Nanoparticle Based Gel of Desoximetasone - Barot, Tularam; Patel, Urja; Barot, Shruti; Dalvadi, Hitesh (International Journal of Pharmaceutical Investigation)
Background: The present study enlightens to enhance the residence time and prolonged release of the desoximetasone by incorporating it into solid lipid nanoparticles (SLN), prepared by hot melt homogenization process. The desoximetasone loaded SLN were incorporated into gel for topical application. Materials and Methods: The preliminary trial batches were carried out by varying the concentration of Poloxamer 188 and lipid concentration. The prepared solid lipid nanoparticles were evaluated for particle size and % entrapment efficiency. From preliminary batches, the levels of Poloxamer 188, Glyceryl Monostearate and Homogenization speed were selected. Desoximetasone loaded SLN were optimized by box-behnken design by Design Expert 10.0.1.0 software. Results: Optimization was done to study influence of X1-amount of lipid, X2-surfactant concentration and X3-speed of homogenization on particle size(Y1), polydispersity index(Y2) and % entrapment efficiency(Y3). From overlay plot, 3.330 g (X1), 0.542 g (X2) and 20930 rpm (X3) were selected. It was observed that there was influence of independent variables over dependent variables. Transmission Electron Microscopy was performed to physically check prepared SLNs. It was observed that majority of SLNs were in the range of 150-200nm. Various parameters like pH, Spreadability, Viscosity, % drug release in 24 hrs of optimized batch was found to be 7.1 ±0.04, 40.99 ± 0. 32g.cm/sec, 10255 ± 18.78 cps, 90.89 ± 0.52% respectively. Accelerated Stability study revealed that there were no significant changes observed upon accelerated stability conditions. Conclusion: Prolonged release of desoximetasone was achieved by preparing desoximetasone loaded SLN based gel for topical application.
Keywords: Box-behnken design; Psoriasis; SLN; Topical dosage form.